Experimental investigation of a novel heat pipe and porous ceramic based indirect evaporative cooler - Amer, Omar; Boukhanouf, Rabah (2016)
The paper presents laboratory test results of an integrated heat pipe and ceramic tube based evaporative cooling prototype for air conditioning in buildings. The cooler integrates durable porous ceramic tubes as water saturated media materials and heat pipes as efficient heat transfer devices. The ceramic tubes and the heat pipes straddle across two separate air ducts to form a wet and dry channel respectively. The thermal performance of the cooler was measured at various air inlet conditions of temperature, humidity and mass flow rates. The experimental measurements show that the cooling system can provide sufficient cooling as high as 1220 W/m2 of the wet media exposed surface area and depressing ambient temperature to 12℃. Equally, it was measured that the wet bulb effectiveness of the cooler can reach 86%.